2021
DOI: 10.1002/tox.23389
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin protects human retinal pigment epithelial cells from high glucose by inhibiting autophagy

Abstract: Purpose The damage of hyperglycemia to the retinal pigment epithelial (RPE) cells is a critical event in diabetic retinopathy (DR). Procyanidin (PC), a kind of polyphenol compounds, has shown to be effective in preventing and treating diabetes as well as its complications, in which autophagy disorder is involved in the pathological mechanism. However, it remains unclear whether PC can play a protective role in DR by regulating the autophagy of RPE. Here, the effect of PC on RPE under high glucose conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…DR is one of the typical diabetes chronic complication, the rise of blood sugar cause serious damage to RPE cells. 23 Recovery of the hyperglycaemia-induced abnormal processes including oxidative stress and inflammation may be helpful to repress the RPE cell damage of DR. 24 According to existing research, it is well recognized that IGF2BP3 can activate the NF-κB signalling pathway and promote pro-inflammatory response. 25 Therefore, in our study, we supplemented the relevant mechanism that the inhibition of IGF2BP3 alleviated the inflammation and apoptosis of the HG-induced RPE cell injury in vitro model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DR is one of the typical diabetes chronic complication, the rise of blood sugar cause serious damage to RPE cells. 23 Recovery of the hyperglycaemia-induced abnormal processes including oxidative stress and inflammation may be helpful to repress the RPE cell damage of DR. 24 According to existing research, it is well recognized that IGF2BP3 can activate the NF-κB signalling pathway and promote pro-inflammatory response. 25 Therefore, in our study, we supplemented the relevant mechanism that the inhibition of IGF2BP3 alleviated the inflammation and apoptosis of the HG-induced RPE cell injury in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…DR is one of the typical diabetes chronic complication, the rise of blood sugar cause serious damage to RPE cells 23 . Recovery of the hyperglycaemia‐induced abnormal processes including oxidative stress and inflammation may be helpful to repress the RPE cell damage of DR 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Zhang et al showed that high glucose conditions mediate the damage to ARPE-19 and increase its autophagy as well as apoptotic markers (p-p53, Bcl-2, and p62), and that these damages can be reversed by the autophagy inhibitor 3-methyladenine (3-MA), indicating a dysregulation of the autophagic process (149). This last observation was further confirmed by the same group, pointing out the beneficial effect of procyanidin, a member of the flavonoids, which inhibits autophagy (150). Interestingly, these beneficial effects were reversed when the autophagy agonist rapamycin was added to procyanidin treatment.…”
Section: The Crosstalk Between Mtor and Autophagy In Drmentioning
confidence: 58%
“…CASP3 has been involved in apoptosis, which cause DR through retinal damage 48 . What's more, under high glucose conditions, the viability of retinal pigment epithelial cells was decreased and the apoptosis rate increased, the expression of CASP3, Bax were increased and the expression of Bcl-2 decreased 49 . Meanwhile, a study found that 50 STZ injection caused the increased expression levels of DNMT1 and DNMT3B, which induced DNA hypermethylation, inhibited the expression of CDKN2B and facilitated the damages of RGC.…”
Section: Constructionmentioning
confidence: 99%